Dapagliflozin attenuates renal gluconeogenic enzyme expression in obese rats - Myat Theingi Swe (2020)
© 2020 Society for Endocrinology The kidneys release glucose into the systemic circulation through glucose reabsorption and renal gluconeogenesis. Currently, the significance of renal glucose release in pathological conditions has become a subject of interest. We examined the effect of sodium-dependent glucose cotransporter 2 inhibitor (SGLT2i) on renal gluconeogenic enzyme expression in obese rats. Male Wistar rats (180-200 g) were fed either a normal diet (ND, n = 6) or a high-fat diet. At 16 weeks, after confirming the degree of glucose intolerance, high-fat diet-fed rats were randomly subdivided into three groups (n = 6/group): untreated group (HF), treated with dapagliflozin 1 mg/kg/day (HFSG) and treated with metformin 30 mg/kg/day (HFM). The treatment was continued for 4 weeks. We observed that dapagliflozin or metformin mitigated the enhanced expression of renal gluconeogenic enzymes, PEPCK, G6Pase and FBPase, as well as improved glucose tolerance and renal function in obese rats. Dapagliflozin downregulated the elevated expression of gluconeogenic transcription factors p-GSK3β, p-CREB and coactivator PGC1α in the renal cortical tissue. Metformin reduced the expression levels of renal cortical FOXO1 and CREB. Furthermore, reduced renal insulin signaling was improved and renal oxidative stress was attenuated by either dapagliflozin or metformin treatment in obese rats. We concluded that glucose tolerance was improved by dapagliflozin in obese prediabetic rats by suppressing renal glucose release from not only glucose reabsorption but also renal gluconeogenesis through improving renal cortical insulin signaling and oxidative stress. The efficacy of dapagliflozin in improving renal insulin signaling, oxidative stress and renal function was greater than that of metformin.